2013
DOI: 10.1186/1472-6831-13-12
|View full text |Cite
|
Sign up to set email alerts
|

Dental sealant knowledge, opinion, values and practice of Spanish dentists

Abstract: BackgroundMultiple guidelines and systematic reviews recommend sealant use to reduce caries risk. Yet, multiple reports also indicate that sealants are significantly underutilized. This study examined the knowledge, opinions, values, and practice (KOVP) of dentists concerning sealant use in the southwest region of Andalusia, Spain. This is a prelude to the generation of a regional plan for improving children’s oral health in Andalusia.MethodsThe survey’s target population was dentists working in western Andalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Therefore, economic variables appear to be one of the reasons for the absence of fissure sealants among adolescents. [16,30,31]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, economic variables appear to be one of the reasons for the absence of fissure sealants among adolescents. [16,30,31]…”
Section: Discussionmentioning
confidence: 99%
“…(2013) concludes that dentists may be underusing fissure sealants, even when knowing that a fissure sealant is effective and has positive effects on the prevention of oral diseases. [16]…”
Section: Introductionmentioning
confidence: 99%
“…according to ICDAS II criteria (0-4). The 120 randomly numbered samples included, 40 sound teeth and 20 teeth in each of the ICDAS II lesion categories (1)(2)(3)(4). Samples were photographed and then radiographed using a wireless Schick digital sensor (3 mA, 70 kVp, 0.050 seconds).…”
Section: Protocolmentioning
confidence: 99%
“…: Spanish data found 48% of the respondents to avoid sealants because they fear to seal carious enamel. 55,56 Only 22% agreed that "sealants, besides being a preventive method, can also have a restorative effect and can be used on incipient carioues lesions". This result clearly showed that, despite two decades of accumulated evidence, the concept of therapeutic sealants have not been adopted in clinical routine.…”
Section: Commented [Sf3]mentioning
confidence: 99%